2019
DOI: 10.1108/ajems-12-2018-0395
|View full text |Cite
|
Sign up to set email alerts
|

Business cycles in Ethiopia under alternative monetary policy rules

Abstract: Purpose The purpose of this paper is to compare business cycle fluctuations in Ethiopia under interest rate and money growth rules. Design/methodology/approach In order to achieve this objective, the author constructs a medium-scale open economy dynamic stochastic general equilibrium (DSGE) model. The model features several nominal and real distortions including habit formation in consumption, price rigidity, deviation from purchasing power parity and imperfect capital mobility. The paper also distinguishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…At the same time, the two-countries RBC model was used to explain cross-country correlations between the loan rates, deposit rates, and loan premiums for both the United States relative to the Euro-area and the United States relative to China (Csabafi et al 2019). Also, a medium-scale open-economy DSGE model was used for a comparative analysis of the volatility of Ethiopia's business cycle under interest rate and money growth rules, where it was found that the model with the money growth rule was essentially less powerful for the transmission of exogenous shocks originating from government spending programs, monetary policy, technological progress, and exchange rate movements (Melesse 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the two-countries RBC model was used to explain cross-country correlations between the loan rates, deposit rates, and loan premiums for both the United States relative to the Euro-area and the United States relative to China (Csabafi et al 2019). Also, a medium-scale open-economy DSGE model was used for a comparative analysis of the volatility of Ethiopia's business cycle under interest rate and money growth rules, where it was found that the model with the money growth rule was essentially less powerful for the transmission of exogenous shocks originating from government spending programs, monetary policy, technological progress, and exchange rate movements (Melesse 2019).…”
Section: Literature Reviewmentioning
confidence: 99%